1901 Cal. Stat. 476 - (:unkn) unknown (My University, 1901)
§ 179: Prohibited the use of a shotgun of larger caliber known as a ten gauge. Violators guilty of a misdemeanor. Possession in the field, on marsh, bay, lake, or stream shall be prima facie evidence of its illegal use.
Keywords: CALIBUR RESTRICTION